EXAMINING THE USE OF VERB TECHNIQUE IN IMPROVING PBI STUDENTS' ABILITY IN FEG CLASS OF THE FOURTH SEMESTER AT UIN ALAUDDIN MAKASSAR - Tri Mandala Putra (Universitas islam Negeri Alauddin Makassar, 2019)
This research aimed at giving a promising sight of students about using verb technique in improving students’ ability in FEG. The research design was quasi experimental with non-equivalent design. It was conducted at the fourth semester of English Education Department at UIN Alauddin Makassar The researcher chose 15 students as experimental class in PBI 1-2 and 15 students as controlled class in PBI 3-4. In the pre-test, the lowest score was only 350, which only had 11 correct answers. After the treatment, examining the use of verb technique, the score of experimental class increased significantly. It proved that the gap of the students’ score of the experimental class between the Pre-test and Post-test was 109. The data illustrated that the treatments gave slightly increasing score in experimental class. Moreover, test of significant testing showed that the value of the t-test was higher than t-table. Therefore, using verb technique is effective in improving PBI students’ ability in FEG class. Based on the fourth chapter, findings and conclusions, it was noted that the technique applied in this research was conceitedly proposed. The students who want to learn structure most used in TOEFL section 2 at the third semester in FEG class was suggested to apply this technique for a better score and know the structure of a long sentence, especially in section 2 which had an important role in scoring the total score of TOEFL. Using verb technique is expected to be broaden. It was the trick which was needed in section 2.